2014
DOI: 10.3389/fendo.2014.00096
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Thyroid Follicular Cells from Pluripotent Stem Cells: Potential for Regenerative Medicine

Abstract: Nearly 12% of the population in the United States will be afflicted with a thyroid related disorder during their lifetime. Common treatment approaches are tailored to the specific disorder and include surgery, radioactive iodine ablation, antithyroid drugs, thyroid hormone replacement, external beam radiation, and chemotherapy. Regenerative medicine endeavors to combat disease by replacing or regenerating damaged, diseased, or dysfunctional body parts. A series of achievements in pluripotent stem cell research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The subsequent manipulation of mES cells has taught us that the first step to programming such cells into a TFC pathway successfully is to lead them to form definitive endoderm. There was subsequently a series of experiments with mouse ES cells trying to obtain fully differentiated ES thyroid follicles (12). Initially, it was found that Activin A, TSH, and IGF1 were capable of inducing some TG expression but only at low levels (2,13).…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent manipulation of mES cells has taught us that the first step to programming such cells into a TFC pathway successfully is to lead them to form definitive endoderm. There was subsequently a series of experiments with mouse ES cells trying to obtain fully differentiated ES thyroid follicles (12). Initially, it was found that Activin A, TSH, and IGF1 were capable of inducing some TG expression but only at low levels (2,13).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid deficiency is common and about 12% of the population in US may suffer the thyroid related conditions during lifetime (Sewell et al, 2014;Agrawal et al, 2015). There have been lots of studies about stem cell technologies which can be the key tools for tissue engineering and regenerative medicine to treat this condition in the recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid gland produces two essential hormones which impact almost every organ and cell of the body and get involved in varieties of biological processes (Sewell et al, 2014). Hypothyroidism, an irreversible change (Ma et al, 2015), is the most common hormonal deficiency and can be precipitated by various diseases (Hollowell et al, 2002;McLachlan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The reprogrammed cells can then be differentiated into any desired cell type and used in cell-based therapy, disease modeling or for drug discovery. Picture adapted from (100).…”
Section: Figure 2 Induced Pluripotent Stem Cellmentioning
confidence: 99%